2012
DOI: 10.4028/www.scientific.net/kem.529-530.391
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Evaluation of Silicon-Containing Apatite Fiber Scaffolds for Bone Tissue Engineering

Abstract: The aim of the present investigation was to examine Si release from the silicon-containing apatite fiber scaffold (Si-AFS) and the biocompatibility of the Si-AFS. We have successfully synthesized silicon-containing apatite fibers (Si-AF) by a homogenous precipitation method. Three-dimensional Si-AFS were fabricated using these Si-AFs. The concentrations of Si in the starting solution were 0 (AF) and 0.8 (0.8Si-AF) mass%. The 0.8Si-AFS1000 were fabricated by firing Si-AF slurry compacts (carbon/Si-AF [w/ ratio:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Recently, we successfully synthesized siliconcontaining apatite fibers (Si-AFs) and fabricated a silicon-containing apatitefiber scaffold (Si-AFS) [11]. Our previous research showed that Si-AFS had a threedimensional cell culture environment and that osteoblastic cells in/on Si-AFS achieved greater proliferation better than those in/on AFS due to eluted Si ions [12,13]. This result is in good agreement with a report by Keeting et al [14].…”
Section: Introductionsupporting
confidence: 88%
“…Recently, we successfully synthesized siliconcontaining apatite fibers (Si-AFs) and fabricated a silicon-containing apatitefiber scaffold (Si-AFS) [11]. Our previous research showed that Si-AFS had a threedimensional cell culture environment and that osteoblastic cells in/on Si-AFS achieved greater proliferation better than those in/on AFS due to eluted Si ions [12,13]. This result is in good agreement with a report by Keeting et al [14].…”
Section: Introductionsupporting
confidence: 88%
“…In addition, we succeeded in synthesizing silicon-containing AF (Si-AF), in which silicon (Si) was added to the abovementioned single-crystal HAp particles with preferred orientation to the c-axis (i.e., AF). 57) Silicon is known to promote bone formation. 58) Porous Si-containing HAp ceramics (hereafter, Si-HAp ceramics) with porosities of 70 and 85 % can be fabricated easily by adding carbon beads with diameters of 20 and 150¯m as pore-forming agents into Si-AFs, follow by firing the green compacts at 1300°C for 5 h in a steam atmosphere.…”
Section: Jcs-japanmentioning
confidence: 99%